2019
DOI: 10.3390/rs11040432
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics of Raindrop Size Distribution in the Monsoon Season Observed in Southern China

Abstract: This study investigates the statistical characteristics of raindrop size distributions (DSDs) in monsoon season with observations collected by the second-generation Particle Size and Velocity (Parsivel2) disdrometer located in Zhuhai, southern China. The characteristics are quantified based on convective and stratiform precipitation classified using the rainfall intensity and total number of drops. On average of the whole dataset, the DSD characteristic in southern China consists of a higher number concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 55 publications
2
56
1
Order By: Relevance
“…The PSD data used in this study were measured by a PARSIVEL disdrometer. This instrument is widely used in the study of worldwide precipitation microphysical characteristics because of its high-cost performance and portability [29]. It was originally primarily developed as a PSD measurement of rainfall and can be used as a weather sensor to distinguish precipitation types [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PSD data used in this study were measured by a PARSIVEL disdrometer. This instrument is widely used in the study of worldwide precipitation microphysical characteristics because of its high-cost performance and portability [29]. It was originally primarily developed as a PSD measurement of rainfall and can be used as a weather sensor to distinguish precipitation types [27].…”
Section: Discussionmentioning
confidence: 99%
“…There are other instruments that can be used to observe precipitation microphysical characteristics, but they also have their own shortcomings. For example, 2DVD can obtain the two-dimensional contour of precipitation particles, but it will underestimate the number of precipitation particles with diameters of less than 0.3 mm [29]; snowflake video imager (SVI) can record the image of snowflakes, but not their fall speeds [22]. To obtain more accurate measurement results, researchers are committed to developing new measurement methods and instruments, such as multiangle snow imager (MASC) [62], and precipitation microphysical characteristics sensor (PMCS) [63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [9] measured the precipitation in Nanjing, China and compared four different methods of rainfall to conclude that the disdrometer and other methods are consistent within the range of medium particle size. However, Zhang et al [10] used three different methods to analyze the DSD characteristics in Zhuhai, China and found that the disdrometer had limitations in measuring small raindrops when compared to other methods. Raupach et al [11] used a 2DVD device to correct the DSDs measured by three disdrometers and the correction showed its general applicability under different climate types.…”
Section: Introductionmentioning
confidence: 99%